(3aJM QH GdHQjI aj Md TQM GdCLQhejIs - (3Ydj Hf YHO GdbGOQ GdfHJHjJjs; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGaY ebGe ef EfNaV dLdGdg hHYO ajbhd Ydi Hf YHO GdbGOQ GdfHfjJi GdMfai bO SCdfi HYV GdCUObGA Cf CVY dg TQMkG dCdaGX TQM GdTjN GdYdGeI NGdO GdCRgQi Ydi GdCLQhejI s
(3BNQgG (B:s
(3hCeG GdEeGdI hGdJUZjQ heG CTHgeG adjS ef GdfMh hGdCLd Pdc de jPcQg aGYde Pdc hGddg JYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs